Integrating LGBTI Inclusivity and Innovative Capacity in India: Analyzing the Effects of Globalization - CHAWLA, Kanika; KUTTY, Nilavathy (Theoretical and Practical Research in Economic Fields, 2024)
Globalization can have enormous effects if LGBTI people are well blended into the pool of resources and tapped efficiently. This research investigates LGBTI inclusivity and the effects of globalization on economic development since the 2009 legalization verdict favoring homosexuality. The theoretical prospects are trifold: trade liberalization and labor market de-regulation; Becker’s theory of discrimination; and Heckscher-Ohlin-Samuelson postulate, along with a diagrammatic representation showcasing the impact of LGBTI inclusivity in the labor market. An OLS approach in conjunction to the ECI_Trade and ECI_Technology has been employed to examine the integration of LGBTI individuals into the Indian economy considering capital stock, domestic credit, employment, population and human capital as default controls to the model and year dummies have been incorporated at a later stage of modelling to highlight the precision level. The study found that LGBTI inclusivity is positively correlated with India's ECI_Trade and ECI_Technology value, increasing it approximately by 6.3% and 15.4%. Further, a number of robustness checks show that even after accounting for macroeconomic variables as default controls, the positive association continues to persist. The LGBTI inclusivity increases the ECI_Trade value by 13.2% and ECI_Technology value by 24.4%, respectively. Consequently, the authors emphasized on the economic ramifications of inclusivity in relation to wage gaps, discrimination, and the development of human capital and have tried to exemplify the integration of LGBTI individuals in EPZs, trade and technological advancement, and skill development to justify the default conceptualized postulates in support of inclusivity.